PARP inhibitors across different malignancies: clinical applications, resistance mechanisms, and strategies to enhance efficacy through combination therapies - Abdelhak Ouhajjou; Omayma Mazouji; Chakib Nejjari; Roberto Incitti; Hicham Mansour (Frontiers in Cell and Developmental Biology, 2026)
Poly-ADP-ribose polymerase (PARP) inhibitors represent a novel class of anticancer agents that leverage the principle of synthetic lethality to induce tumor cell death by disrupting defective DNA repair pathways. PARP inhibitors have demonstrated strong preclinical activity in tumors with homologous recombination (HR) repair deficiencies. The discovery of synthetic lethality between HR defects and PARP inhibition led to multiple clinical trials, first in BRCA1/2-mutated cancers and later in other HR-deficient tumors. PARP inhibitors have become essential components of first- and later-line therapies for breast, prostate, pancreatic, and ovarian cancers, with several agents already approved by the FDA. However, their therapeutic potential in other malignancies remains less defined, as limited studies have explored their efficacy in additional solid tumors. This article provides an updated overview of PARP inhibitors use beyond their established clinical indications, highlighting current evidence, combination strategies, and emerging perspectives that may expand their role in various cancer treatment including endometrial cancer, cervical cancer, kidney cancer, colorectal cancer, non–small cell lung cancer (NSCLC), small cell lung cancer (SCLC) and other malignancies.